Optimal load maximizes the mean mechanical power output during upper extremity exercise in highly trained soccer players - Jandacka, Daniel; Uchytil, Jaroslav (Journal of strength and conditioning research, 2011)
The purpose of this study was to determine the optimal load for the maximal power output during the acceleration phase of a power movement in bench press (BP) exercises of highly trained soccer players at the beginning of a competition period. Fifteen professional male soccer players with an average age of 26.1 ± 3.9 years, an average height of 183.3 ± 6.7 cm, an average body mass of 78.8 ± 7.2 kg, and an average 1 repetition maximum (1RM) of 83.3 ± 11.2 kg were employed as subjects in this study. Maximal mean power output during a BP at 0, 10, 30, 50, 70, and 90% of their 1RM was measured to determine whether an optimal load exists that allows for the attainment of maximal power output. Three-dimensional upper extremity kinematic data were collected. Two force plates embedded in the floor and positioned below the bench were used to measure contact forces between the bench and ground during the lift. A repeated-measures analysis of variance was performed to determine power output differences at different percentages of the 1RM. The results of this study indicated that loads of 50% of the 1RM resulted in greater mean power output during the complete positive power movement. Loads at 30 and 50% of the 1RM resulted in greater mean power output computed from the acceleration phase of the lift than did all loads and were not statistically different from each other. However, individual soccer players did not reach the maximum power output with the same relative load. In conclusion, when soccer players develop muscular power toward the end of when the most important competitions are scheduled, dynamic effort strength training with the range of load from 30 to 50% of 1RM BP should be used. During the competition period, a load of 50% of a 1RM should be used in a BP to maintain muscular power over a wide load range.
Keywords: fotbal; zatížení muskuloskeletálního systému; biomechanika; svalová síla; Soccer; Upper Extremity; Weight Lifting; sportovci; fyzická vytrvalost; cvičení; Biomechanical Phenomena; mužské pohlaví; Muscle, Skeletal; Adult; mladý dospělý; Weight-Bearing; vzpírání; Athletes; Muscle Strength; Young Adult; Humans; Physical Endurance; kosterní svaly; Exercise; dospělí; horní končetina; lidé; Male